BlockLens: visual analytics of student coding behaviors in block-based programming environments. - TUNG, Sean (Institutional Knowledge at Singapore Management University, 2022)
Block-based programming environments have been widely used to introduce K-12 students to coding. To guide students effectively, instructors and platform owners often need to understand behaviors like how students solve certain questions or where they get stuck and why. However, it is challenging for them to effectively analyze students’ coding data. To this end, we propose BlockLens, a novel visual analytics system to assist instructors and platform owners in analyzing students’ block-based coding behaviors, mistakes, and problem-solving patterns. BlockLens enables the grouping of students by question progress and performance, identification of common problem-solving strategies and pitfalls, and presentation of insights at multiple granularity levels, from a high-level overview of all students to a detailed analysis of one student’s behavior and performance. A usage scenario using real-world data demonstrates the usefulness of BlockLens in facilitating the analysis of K-12 students’ programming behaviors.